2018
DOI: 10.1039/c8fo00348c
|View full text |Cite
|
Sign up to set email alerts
|

Science behind the cardio-metabolic benefits of omega-3 polyunsaturated fatty acids: biochemical effectsvs. clinical outcomes

Abstract: Lower incidence of cardiovascular disease (CVD) in the Greenland Inuit, Northern Canada and Japan has been attributed to their consumption of seafood rich in long chain omega-3 polyunsaturated fatty acids (LCn-3PUFA). While a large majority of pre-clinical and intervention trials have demonstrated heart health benefits of LCn-3PUFA, some studies have shown no effects or even negative effects. LCn-3PUFA have been shown to favourably modulate blood lipid levels, particularly a reduction in circulating levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 265 publications
1
31
0
Order By: Relevance
“…In vitro studies showed that LCn-3PUFA improved endothelial function [143]. Although a fall in mortality from CVDs, most deaths are caused by sudden cardiac deaths associated with fatal arrhythmia [144]. The antiarrhythmic actions of LCn-3PUFA have been shown in vitro using cultured neonatal cardiac myocytes.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…In vitro studies showed that LCn-3PUFA improved endothelial function [143]. Although a fall in mortality from CVDs, most deaths are caused by sudden cardiac deaths associated with fatal arrhythmia [144]. The antiarrhythmic actions of LCn-3PUFA have been shown in vitro using cultured neonatal cardiac myocytes.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…The main finding emerging from different studies is that ω-3 PUFAs counterbalance CVD risk factors in a genderspecific manner, both in primary and secondary prevention [103]. A meta-analysis indicated that dietary intake of fish and ω-3 PUFAs was correlated with lower incidence and mortality of stroke, especially in women and those with body mass index ðBMIÞ < 24 kg/m 2 [104].…”
Section: Intervention Studiesmentioning
confidence: 99%
“…Omega-6 and Omega-3 supplements can as well be manufactured from laboratories and sold as pharmaceutical medicine. Sufficient consumption of foods rich in PUFAs, such as Omega-3 and Omega-6, influences the occurrence of inflammation in the body as well as cardio-metabolic health status in individuals [14].…”
Section: Effects Of Omega-3 and Omega-6 On Inflammation And Cardio-mementioning
confidence: 99%